2017
DOI: 10.1186/s13071-017-2496-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Trichomonas vaginalis isolates by actin gene sequence analysis and carriage of T. vaginalis viruses

Abstract: BackgroundThe protozoan parasite Trichomonas vaginalis is the most common non-viral, sexually transmitted pathogen. Although T. vaginalis is highly prevalent among women in Kenya, there is lack of data regarding genetic diversity of isolates currently in circulation in Kenya.MethodsTyping was performed on 22 clinical isolates of T. vaginalis collected from women attending the antenatal care clinic at Kilifi County Hospital, Kenya, in 2015. Genotyping followed a previously proposed restriction fragment length p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
3
13
1
2
Order By: Relevance
“…These results are similar to a study of TV-infected women in India, in which TVV+ isolates were not associated with genital symptoms [30]. A Kenyan study of TV-infected women also found no association between genital symptoms and TVV+ isolates [31]. In contrast, a Cuban study of 37 TV isolates found an association between the presence of genital symptoms and signs and TVV positivity among 21 isolates that were TVV+ (P < .01) [32].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are similar to a study of TV-infected women in India, in which TVV+ isolates were not associated with genital symptoms [30]. A Kenyan study of TV-infected women also found no association between genital symptoms and TVV+ isolates [31]. In contrast, a Cuban study of 37 TV isolates found an association between the presence of genital symptoms and signs and TVV positivity among 21 isolates that were TVV+ (P < .01) [32].…”
Section: Discussionsupporting
confidence: 80%
“…El-Gayar et al [27] also found a significant association between TVV positivity and clinical manifestations of trichomoniasis among 40 TV-infected women in Egypt. However, the sample sizes of these studies were small and the associations between genital symptoms and TVV+ isolates have not been seen in larger studies, including our present study [28,30,31].…”
Section: Discussionmentioning
confidence: 61%
“…Although actin genotypes A and P of T. vaginalis have been found in previous studies, neither were identified in the targeted population [ 14 ]. In Kenya, five actin genotypes were revealed by RFLP analysis in 2015, and 50.0% of the isolates were of actin genotype E, 27.3% of actin genotype N, 13.6% of actin genotype G and 4.5% of actin genotypes I and P [ 21 ]. Based on 18S rRNA gene sequences, genetic variants among T. vaginalis were found in the cities of Anyang, Zhengzhou, Shangqiu, Luoyang, Pingdingshan, Zhumadian and Xinyang, Henan Province, China, and the results indicated that the T. vaginalis isolates identified could be regarded as a single population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Можно отметить, что в большинстве исследований наиболее распространенными генотипами являются генотипы E и G. Исключением является только исследование Matini et al (2017) [5] с 56% генотипа А. В украинской популяции отмечается доминирование генотипа Е, выраженное больше, чем в других исследованиях (68,96%). Сходное, хотя и менее выраженное доминирование ДЕРМАТОЛОГіЯ та вЕнЕРОЛОГіЯ генотипа Е было выявлено Crucitti et al [9] в Конго (55,7%) и Masha S. C. et al [10] в Кении (50%). В целом, в наибольшей степени показатели украинской популяции сходны с данными, полученными Crucitti et al в Конго [9].…”
Section: результаты и их обсуждениеunclassified
“…Необходимо отметить, что, по результатам исследования Masha S. C. et al [10], трихомонады, относящиеся к генотипу Е, обладают рядом биологических особенностей, среди которых -клональная стабильность и низкий уровень инфицирования вирусами. Возможно, эти особенности генотипа Е могут быть связаны с его высокой распространенностью в украинской популяции.…”
Section: результаты и их обсуждениеunclassified